The impact of COVID-19 and construction business survival strategies: a review / Nur Hidayah Mohamed and Musmuliadi Kamaruding - Mohamed, Nur Hidayah; Kamaruding, Musmuliadi (2023)
The outbreak of Covid-19 in late 2019 had a significant impact on all industries worldwide, including the construction business. This review paper aims to explore the impacts of Covid-19 on the construction business and to identify survival strategies for construction businesses during this pandemic. The study is based on selected articles to achieve its objectives. The review reveals several impacts of Covid-19 on the construction business survival, including financial difficulties, project delays, problems with material resources, and increased construction costs. To mitigate these impacts, several strategies have been identified that construction companies can adopt. These include adhering to guidelines from government authorities and the WHO, effective communication with customers, flexible human resource management, prioritizing technology, emphasizing health and safety aspects, being knowledgeable and prepared for the pandemic's impact, exploring new markets, and taking advantage of financial assistance provided by the government and banks. Ultimately, this study aims to provide beneficial insights to society, particularly for construction companies and researchers.